Responsiveness of quality‐of‐life measures in patients with peripheral vascular malformations: the OVAMA project. (1st June 2020) - Lokhorst, M.M.; Horbach, S.E.R.; Waner, M.; O, T.M.; van der Vleuten, C.J.M.; Mokkink, L.B.; van der Horst, C.M.A.M.; Spuls, P.I.
Summary: Background: The OVAMA (Outcome Measures for Vascular Malformations) project determined quality of life (QoL) as a core outcome domain for patients with vascular malformations. In order to measure how current therapeutic strategies alter QoL in these patients, a patient‐reported outcome measurement (PROM) responsive to changes in QoL is required. Objectives: To assess the responsiveness of two widely used generic QoL PROMs, the Medical Outcomes Study Short Form 36 (SF‐36) and Skindex‐29, in adult patients with vascular malformations. Methods: In an international multicentre prospective study, treated and untreated patients completed the SF‐36 and Skindex‐29 at baseline and after a follow‐up period of 6–8 weeks. Global rating of change (GRC) scales assessing various QoL‐related outcome domains were additionally completed. Per subscale, responsiveness was assessed using two methods: by testing hypotheses on expected correlation strength between change scores of the questionnaires and the GRC scales, and by calculating the area under the receiver operating characteristics curve (AUC). The questionnaires were considered responsive if ≥ 75% of the hypotheses were confirmed or if the AUC was ≥ 0·7. Results: Eighty‐nine participants were recruited in three centres in the Netherlands and the U.S.A., of whom 67 completed all baseline and follow‐up questionnaires. For all subscales of the SF‐36 and Skindex‐29, < 75% of the hypotheses were confirmed and the AUC was < 0·7. Conclusions: Our findings suggest that the SF‐36 and Skindex‐29 seemed unresponsive to change in QoL. This suggests that alternative PROMs are needed to measure – and ultimately improve – QoL in patients with vascular malformations. What's already known about this topic? Quality of life is often impaired in patients with vascular malformations. Quality of life is considered a core outcome domain for evaluating treatment of vascular malformations. To measure the effect of treatment on quality of life, a patient‐reported outcome measure is required that is responsive to changes in quality of life. What does this study add? This is the first study assessing the responsiveness of quality‐of‐life measures in patients with vascular malformations. The results seem to indicate that the Medical Outcomes Study Short Form 36 (SF‐36) and Skindex‐29 are not responsive to changes in quality of life in patients with vascular malformations. What are the clinical implications of this work? Medical Outcomes Study Short Form 36 (SF‐36) and Skindex‐29 are not ideal to assess the effect on quality of life over time, of treatment strategies for peripheral vascular malformations.